Management and prediction of immune-related adverse events for PD1/PDL-1 immunotherapy in colorectal cancer - Sun, Liting; Meng, Cong; Zhang, Xiao; Gao, Jiale; Wei, Pengyu; Zhang, Jie; Zhang, Zhongtao (Frontiers in Pharmacology, 2023)
Programmed cell death protein (PD-1) is an important immunosuppressive molecule, which can inhibit interaction between PD-1 and its ligand PD-L1, further enhancing the T cell response and anti-tumor activity, which is called immune checkpoint blockade. Immunotherapy, represented by immune checkpoint inhibitors, has opened up a new era of tumor treatment and is gradually being applied to colorectal cancer recently. Immunotherapy was reported could achieve a high objective response rate (ORR) for colorectal cancer with high microsatellite instability (MSI), thus opening up a new era of colorectal cancer immunotherapy. Along with the increasing use of PD1 drugs in colorectal cancer, we should pay more attention to the adverse effects of these immune drugs while seeing the hope. Immune-related adverse events (irAEs) caused by immune activation and immune homeostasis during anti-PD-1/PD-L1 therapy can affect multi-organ and even be fatal in serious cases. Therefore, understanding irAEs is essential for their early detection and appropriate management. In this article, we review the irAEs that occur during the treatment of colorectal cancer patients with PD-1/PD-L1 drugs, analyze the current controversies and challenges, and point out future directions that should be explored, including exploring efficacy predictive markers and optimizing the paradigm of individualized immunotherapy.